Novel 3D ultrasound system for midline single-operator epidurals: a feasibility study on a porcine model. (May 2017) - Stone, J.; Beigi, P.; Rohling, R.; Lessoway, V.; Dube, A.; Gunka, V.
Highlights: Novel method of single operator, midline, real-time ultrasound guided lumbar epidural. High success rate of epidural placement. Success further improved by echogenic needle use. Abstract: Background: We developed a real-time 3D ultrasound thick slice rendering technique and innovative Epiguide needle-guide as an adjunct to single-operator midline epidural needle insertions. Study goals were to determine feasibility of the technique in a porcine model and compare the visibility of standard and echogenic needles. Methods: Thirty-four lumbar needle insertions were performed on six intact porcine spines ex vivo . Ultrasound scanning identified the insertion site and, using an Epiguide, the needle was guided into the epidural space through the ligamentum flavum in the midline plane, watched in real-time on the 3D ultrasound. Entry into the epidural space was judged by a loss-of-resistance technique. Needle visibility was rated by the anesthesiologist performing the technique using a 4-point scale; (0=cannot see, 1=poor, 2=satisfactory, 3=excellent), and later by an independent assessor viewing screenshots. The procedure was repeated at all lumbar levels using either the standard or echogenic needle. Results: Successful loss-of-resistance to fluid was achieved in 76% of needle insertions; needle visibility with echogenic needles (94.2% rated satisfactory/excellent) was significantly better than with standard needles (29.4% satisfactory/excellent, P  <0.0001). Successful loss-of-resistance was 93% when mean needle visibility was rated as 'excellent'. Inter-observer agreement between assessors was 'near-perfect' (weighted kappa=0.83). Conclusion: It is feasible to perform 3D ultrasound-guided real-time single-operator midline epidural insertions, in a porcine model. Echogenic needles were found to consistently improve needle visibility; and improved needle visibility tended to increase successful entry into epidural space.